FEMINIST STYLISTICS IN AHDAF SOUEIF’S AISHA - Aasadi, Rana (Fırat University, 2023)
Deconstructing meanings and their accepted interpretations are the primary goals of stylistics. Feminist stylistics is mainly based on feminist theories, which are particularly interested in patriarchal norms that marginalize and degrade women. This study examines the feminist discourse in Ahdaf Soueif’s short story collection Aisha, which is one of the significant works portraying Arab women in a patriarchal culture. Asian women's difficulties are covered in the feminist book Aisha. By putting gender issues at the center of the textual analysis, feminist stylistics exposes the untenable assumptions of traditional stylistics. This feminist approach highlights gender discourses in various texts, including linguistic and thematic disparities. In light of this, the study will explain feminist stylistics, provide a brief overview of Ahdaf Soueif's biography, and use a feminist stylistic approach to Soueif's stories. The author hopes to demonstrate how language's treatment of gender reflects patriarchal culture. In order to evaluate sexism and patriarchal issues in the stories and how point of view, agency, metaphor, or transitivity are tied explicitly to gender by separating women's writing habits from men's writing, this study will use feminist stylistics to analyse the stories at word/phrase, sentence, and discourse level.

Anlamları ve bunların kabul edilen yorumlarını yapısökümüne uğratmak, biçembilimin birincil hedefleridir. Feminist üslup esas olarak, özellikle kadınları marjinalleştiren ve aşağılayan ataerkil normlarla ilgilenen feminist teorilere dayanmaktadır. Bu çalışma, ataerkil bir kültürde Arap kadınını betimleyen önemli eserlerden biri olan Ahdaf Soueif'in kısa öykü derlemesi Aisha'daki feminist söylemi incelemektedir. Asyalı kadınların zorlukları feminist kitap Aisha'da anlatılıyor. Feminist üslup bilimi, toplumsal cinsiyet konularını metinsel analizin merkezine koyarak, geleneksel üslup biliminin savunulamaz varsayımlarını teşhir eder. Bu feminist yaklaşım, dilbilimsel ve tematik eşitsizlikler de dahil olmak üzere çeşitli metinlerdeki toplumsal cinsiyet söylemlerini vurgular. Bunun ışığında, çalışma feminist üslubu açıklayacak, Ahdaf Soueif'in biyografisine kısa bir genel bakış sunacak ve Soueif'in hikayelerine feminist bir üslup yaklaşımı kullanacak. Yazar, dilin toplumsal cinsiyeti ele alış biçiminin ataerkil kültürü nasıl yansıttığını göstermeyi umuyor. Hikâyelerdeki cinsiyetçiliği ve ataerkil meseleleri ve kadınların yazma alışkanlıklarını erkeklerin yazma alışkanlıklarından ayırarak bakış açısının, failliğin, mecazın veya geçişliliğin açıkça toplumsal cinsiyete nasıl bağlandığını değerlendirmek için bu çalışma, feminist üslubu kullanarak öyküleri kelime/anahtarda analiz edecektir. ifade, cümle ve söylem düzeyi.
AHDAF SOUEIF’IN ROMANI AISHA’DA FEMİNİST BİÇEMBİLİM
Keywords: Stylistics and Textual Analysis; Stilistik ve Metinsel Analiz